Decomposition pathways of polytetrafluoroethylene by co-grinding with strontium/calcium oxides. Issue 11 (3rd June 2017) - Qu, Jun; He, Xiaoman; Zhang, Qiwu; Liu, Xinzhong; Saito, Fumio
ABSTRACT: Waste polytetrafluoroethylene (PTFE) could be easily decomposed by co-grinding with inorganic additive such as strontium oxide (SrO), strontium peroxide (SrO2 ) and calcium oxide (CaO) by using a planetary ball mill, in which the fluorine was transformed into nontoxic inorganic fluoride salts such as strontium fluoride (SrF2 ) or calcium fluoride (CaF2 ). Depending on the kind of additive as well as the added molar ratio, however, the reaction mechanism of the decomposition was found to change, with different compositions of carbon compounds formed. CO gas, the mixture of strontium carbonate (SrCO3 ) and carbon, only SrCO3 were obtained as reaction products respectively with equimolar SrO, excess SrO and excess SrO2 to the monomer unit CF2 of PTFE were used. Excess amount of CaO was needed to effectively decompose PTFE because of its lower reactivity compared with strontium oxide, but it promised practical applications due to its low cost.